IMPLEMENTASI TOTAL QUALITY MANAGEMENT (TQM) DI PERGURUAN TINGGI - Jihaduddin (Kaffah: Jurnal Pendidikan dan Sosio Keagamaan, 2023)
Nowadays the management of University headed to the system of management that colled Total Quality Management, or Integration Quality Management. Basicly the system of management is controller of all organization in university activity. Application of Total Quality Management, means all of the Committee Responsible of education quality. The university is not so different with the company organization, it also has “costumers” who are the user of the product. “Costumers” are “internal costumers” who are the subject of product process, and “eksternal costumers” who are the user of the product.